In vitro micropropagation of Bromelia balansae Mez.: effects of light intensity and growth regulators on plant development (Research, Society and Development, 2023)
We detail herein the in vitro micropropagation of Bromelia balansae Mez. In this regard, we investigated the germination and the action of growth regulators in inducing callogenesis. Furthermore, we thoroughly investigated the influence of light intensity on plant growth as well as the production of secondary metabolites. The germination rate of B. balansae seeds was 94.95% and the developed seedlings were uniform. It was possible to observe that the amount of callus formed per explant was influenced by the concentrations and combinations of distinct growth regulators. Furthermore, it was possible to observe variations in the concentration of total phenolic compounds and flavonoids in the extracts of the plants cultivated under different light intensities. Therefore, this study showcases the effect of growth conditions in the morphology and chemical constitution of in vitro grown B. balansae.